Refleksyjność młodzieży wobec własnej przyszłości zawodowej - Myszka-Strychalska, Lucyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The realm of professional life is an important segment of the existence of each human being, which requires proper consideration and engagement on their behalf. Planning, management and tracking one’s own career are ones of those tasks that each individual faces throughout their life. It turns out to be extremely interesting to observe how the youth accomplish that assignment, because the young people of today are the future creators of the labour market. While they are preparing themselves for a changeable and unpredictable reality, they also reflect on their own future and, thereby, try to establish their place in the world. This reflectiveness, being the basic attribute of human actions, showing their self-awareness and making it possible to give the reasons for how they are carrying out their undertakings, could be an inspiring subject of empirical research.
Keywords: career; occupational choice; planning for the professional future; reflexivity; youths